2022
DOI: 10.18097/pbmc20226803218
|View full text |Cite
|
Sign up to set email alerts
|

Contents of BDNF, miR-30a-5p and miR-122 during alcohol withdrawal syndrome

Abstract: Some BDNF (brain-derived neurotrophic factor)-targeted microRNAs such as miR-30a-5p associate with alcohol dependence phenomenon however their relationship with AWS is not described. We aimed to measure serum BDNF concentration and relative content of miR-30a-5p over the course of alcohol abstinence and compare obtained results with clinics of AWS. Additionally, we studied relative serum content of miR-30a-5p, a microRNA which does not target BDNF but relates to alcohol use disorder. Serum BDNF concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We investigated the effects of BDNF rs6265 and FGF21 rs11665896 on impulsivity with alcohol dependence during withdrawal. Previous studies showed that BDNF played a significant role in the processes of alcohol withdrawal syndrome ( 31 ), and FGF21 is related to AUD ( 32 ). The present study found no significant single-gene effect of BDNF rs6265 or FGF21 rs11665896 on AUD-related impulsivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the effects of BDNF rs6265 and FGF21 rs11665896 on impulsivity with alcohol dependence during withdrawal. Previous studies showed that BDNF played a significant role in the processes of alcohol withdrawal syndrome ( 31 ), and FGF21 is related to AUD ( 32 ). The present study found no significant single-gene effect of BDNF rs6265 or FGF21 rs11665896 on AUD-related impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that BDNF and FGF21 are associated with alcohol dependence and impulsivity ( 31 , 32 ). In addition, the link between BDNF SNP and AUD has been reported in some critical literature.…”
Section: Introductionmentioning
confidence: 99%